How Does Metformin as First-Line Therapy Impact Long-Term Cardio- Vascular and Metabolic Outcomes in Patients with Type 2 Diabetes Mellitus over A 5-Year Period ? : A Systematic Review - Firman Gustina; Amelinda Nur Amalina; Fajar Nugraha; Fitriah Hany (The International Journal of Medical Science and Health Research, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder requiring effective long-term management strategies.  Metformin is established as a first-line therapy, and understanding its long-term (≥5 years) cardiovascular and metabolic implications is crucial for optimizing patient care.  This systematic review aimed to synthesize existing academic literature on these long-term outcomes. Methods: This systematic review adhered to PRISMA 2020 guidelines. Results: Metformin demonstrated significant long-term cardiovascular benefits, including a notable reduction in heart failure incidence (Hazard Ratio [HR] 0.51)  and a lower overall cardiovascular risk (Odds Ratio [OR] 0.57).  Effects on specific events like myocardial infarction were modest (e.g., Risk Ratio [RR] 0.89, HR 0.88), and results for stroke were varied, though benefits were observed in specific subgroups such as patients with chronic kidney disease (CKD) (RR 0.76 for cardiovascular events)  or post-stroke (OR 0.66 for poor course).  Metabolically, metformin consistently led to reductions in HbA1c (ranging from 0.06% to 1.13%), modest decreases in BMI (up to 0.46 kg/m²), and reductions in LDL cholesterol (around 5-6 mg/dL).  Discussion: The substantial reduction in heart failure incidence and overall cardiovascular risk highlights metformin's role in primary prevention in T2DM patients.  While the impact on specific major adverse cardiovascular events like myocardial infarction and stroke is more nuanced, clear benefits emerge in high-risk subgroups.  Sustained improvements in glycemic control are crucial for long-term complication reduction.  Conclusion: First-line metformin therapy is associated with favorable long-term cardiovascular and metabolic profiles in adults with T2DM over five years or more.  Key benefits include significant reductions in heart failure incidence, improved overall cardiovascular risk, consistent glycemic control, and modest weight and lipid improvements.  Its well-established safety record, including a lower risk of hypoglycemia compared to sulfonylureas and manageable side effects with formulation adjustments, solidifies its foundational role in the comprehensive, long-term management of T2DM.